The Substance View: A Critique (Part 3). (23rd December 2016) - Lovering, Rob
ABSTRACT: In my articles 'The Substance View: A Critique' and 'The Substance View: A Critique (Part 2), ' I raise objections to the substance view (naturally), a theory of intrinsic value and moral standing defended by a number of contemporary moral philosophers, including Robert P. George, Patrick Lee, Christopher Tollefsen, and Francis Beckwith. In part one of my critique of the substance view, I raise reductio‐style objections to the substance view's conclusion that the standard human fetus has the same intrinsic value and moral standing as the standard adult human being, among other human beings. In part two, I raise objections to some of the premises invoked in support of that conclusion. Here, in part three, I raise objections to Henrik Friberg‐Fernros's attempt to rebut some of the aforementioned objections.